(untitled) - McQuail, Denis (London, 1995)
The book bridges the gap between the study of mass media and wider questions of politics and society; it also effectively combines normative theory and empirical research. It examines the tension between the objectives of cohesion and social harmony, and those of media freedom and diversity
Keywords: Instruction materials personel,Social interaction